Fluttering Effect of 3D Printing Part - MUHAMMAD DANIAL,; SITI JUITA MASTURA, (Research Progress in Mechanical and Manufacturing Engineering, 2022)
3D printing is an innovation in manufacturing industries that has the potential to usher in a new industrial look. Nevertheless, this technology has some limitations, for instance, the fluttering effect occurrence which being a crucial effect to obtain a good result. In this regard, the present study is aimed to identify the fluttering effect in order to prevent damaged printing parts during the 3D printing process. Three target quality parameters and six factors were chosen to be examined experimentally. In addition, three materials and two types of printers were used in this experiment in order to observe and derived the result from the evaluation of the 3D printing system. The result indicates that fluttering effects occur on few samples based on the observation made from target parameters chosen in terms of surface quality, warping and shifting layer. The presence of fluttering effects was analyzed in 5 out of 27 samples showing poor quality results It can be concluded that the model dimension and environmental error such as vibration on extruder during printing process are the main factors to the occurrence of fluttering effects.